Design, fabrication and characterization of micro combustor for micro gas turbine engine - Alwar Vasanthakumar (2008)
The demands of portable power sources are growing up simultaneously with the growth in the production of more and more portable devices. This work paves way to the development of compact, low cost, portable power generation systems to fulfill the above demand. This thesis report describes about the design, fabrication and testing of microfabricated devices such as the micro-combustor and the micro-turbine, which are then integrated to form the microgasturbine engine for the production of electrical power.